PENGABDIAN KEPADA MASYARAKAT USAHA KERIPIK SINGKONG “CAHAYA BANGKA” RASA PEDAS MANIS (MIXER MACHINE) - Yudi Oktriadi; Husman Husman; Zulfitriyanto Zulfitriyanto; Achmad Afriadi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Cassava chips are one of the most popular snack products in various walks of life. The raw material for cassava chips is made from thinly sliced ??cassava. In the process of making cassava chips, there are many processes that are passed in the form of slicing cassava into thin, then fried, dried, Mixed together with flavoring and packaging. From a survey that has been conducted on partners, the process of mixing cassava chips that have been fried with spices is the main problem because the mixing process is still manual, that is, it uses human power and it takes time for the stirring process to take quite a bit of energy, which is for approximately 10 minutes to stir the spices with the number of chips stirred 2-3 kg and carried out by one person, this drains a lot of energy and time. From this problem, as the proponent of the Educational Institution will make a cassava chip spice mixer machine that can replace human labor, so that capacity and time can be increased. Partners will get appropriate technology in the form of a cassava chip spice mixer machine and training on the process of using the machine and maintaining the machine. In addition, Partners will always receive maintenance services if the machine provided is disturbed or damaged. To achieve this goal, the Partners and the Service team agreed to propose to increase the quality and production capacity. The development of the production process is carried out by providing cassava chips seasoning mixing machine technology with a total of 5 kg of cassava chips stirred in 10 minutes.